Baclofen reversed thermal place preference in rats with chronic constriction injury - Salte, K; Lea, G; Franěk, Miloslav; Vaculín, Šimon (Physiological research, 2016)
Chronic constriction injury to the sciatic nerve was used as an animal model of neuropathic pain. Instead of frequently used reflex-based tests we used an operant thermal place preference test to evaluate signs of neuropathic pain and the effect of baclofen administration in rats with neuropathy. Chronic constriction injury was induced by four loose ligations of the sciatic nerve. Thermal place preference (45 °C vs. 22 °C and 45 °C vs. 11 °C) was measured after the ligation and after the administration of baclofen in sham and experimental rats. Rats with the chronic constriction injury spent significantly less time on the colder plate compared to sham operated animals at the combination 45 °C vs. 11 °C. After administration of baclofen (10 mg/kg s.c.), the aversion to the colder plate in rats with chronic constriction injury disappeared. At the combination 45 °C vs. 22 °C, no difference in time spent on colder and/or warmer plate was found between sham and experimental animals. These findings show the importance of cold allodynia evaluation in rats with chronic constriction injury and the effectiveness of baclofen in this neuropathic pain model.
Keywords: centrálně působící myorelaxancia; potkani Wistar; Male; konstrikce; Sciatic Neuropathy; Rats, Wistar; měření bolesti; krysa rodu Rattus; Muscle Relaxants, Central; vysoká teplota; Peripheral Nervous System Diseases; Rats; operantní podmiňování; Cold Temperature; nemoci sedacího nervu; Hot Temperature; zvířata; mužské pohlaví; Pain Measurement; nemoci periferního nervového systému; baklofen; Animals; Conditioning, Operant; Baclofen; Constriction; nízká teplota